Determinan Pendapatan Pedagang Pasar Tradisional Di Kota Palangka Raya - Herman Fland Dakhi; Kezia Tamba; Ristauli Siregar; Arum Widiyasyar; Joel Manurung; Suherman Suherman (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This study was conducted with the aim of understanding the elements that influence the income of traditional market traders in Palangka Raya City. The method used in this research is a quantitative method using surveys as a tool for collecting information. The participants in this research are people who work as traders in traditional markets in Palangka Raya City. Research reveals that the income of traditional market traders in Palangka Raya City is influenced by several factors, including market location, type of product sold, and the amount of capital they own. Apart from that, research also reveals that these factors have a strong influence on the income of traders in traditional markets in Palangka Raya City.